IPD-OUM Certificate Presentation Ceremony - Anuwar Ali, (Open University Malaysia (OUM), 2003)
Speech of the President/Vice-Chancellor OUM, Prof Tan Sri Anuwar Ali on collaborative programme with Jaya Jusco at PWTC. 12 December 2003.